Mathmatters : - Lynch, Chicha (National textbook Company, 1998)
Math Matters is designed to help all your students succeed. Rather than isolating the branches of mathematics, this three-book program reinforces the connections between algebra and geometry while developing problem-solving skills. This comprehensive program includes: Teacher's Annotated Edition, Student Supplement (English and Spanish), Overhead Transparencies, Tests, Assessment Options, Answer Key, MicroExam II for Apple, Mac, and IBM formats, and Teacher's Resources.